2013
DOI: 10.1021/jo400152f
|View full text |Cite
|
Sign up to set email alerts
|

TMEDA-Assisted Effective Direct Ortho Arylation of Electron-DeficientN-Heteroarenes with Aromatic Grignard Reagents

Abstract: In the addition of TMEDA in toluene, aryl Grignards could effectively and site-specifically ortho-arylate electron-deficient heteroarenes under mild conditions. This endeavor successfully changed the old low-yielding reaction, aryl Grignard addition to N-heteroarenes, into an efficient procedure for heterobiaryls. The combination of the inexpensive aryl Grignards, TMEDA, the cost-free air, no use of any transition-metal catalyst, the mild reaction conditions, and the high-yielding gram-scale results enables th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…Zhuo et al [18] reported the synthesis of herteobiaryls by the reactions of ArMgX 21 and hetero aryls 22-25 in the presence of TMEDA and toluene. In conclusion, they have demonstrated that TMEDA could efficiently enhance the direct o-arylation of electron-deficient hetero N-arenes with ArMgX under mild conditions.…”
Section: Arylation Via Grignard Reagent-mediated Reactionmentioning
confidence: 99%
“…Zhuo et al [18] reported the synthesis of herteobiaryls by the reactions of ArMgX 21 and hetero aryls 22-25 in the presence of TMEDA and toluene. In conclusion, they have demonstrated that TMEDA could efficiently enhance the direct o-arylation of electron-deficient hetero N-arenes with ArMgX under mild conditions.…”
Section: Arylation Via Grignard Reagent-mediated Reactionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38] The synthesis of the latter quinoline was achieved therough Sonogashira coupling by using the typical [PdCl 2 (PPh 3 ) 2 ]/ CuI system, [31] Suzuki cross-coupling, [32] iron-catalyzed Fe(acac) 3 cross-coupling of aromatic Grignard reagent (2-thienylmagnesium bromide) with 2-chloroquinoline, [33] and through reaction of quinoline with 2-thienylmagnesium bromide in the presence of TMEDA. [34] Furthermore, 2-thiophenyl-4-aryl-disubstituted quinolines obtained by Sonogashira coupling from acyl chlorides, alkynes, and 2-aminothiophenols using the [PdCl 2 (PPh 3 ) 2 ]/CuI system [35] have also been reported. Moreover, quinoline derivatives with the thienyl motif in other positions of the quinoline moiety are known; their synthesis has been mainly performed by modified Suzuki coupling.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with the observation of TMEDA-catalyzed arylation of azines with arylmagnesium bromides reported by Da. 8 No functionalization of the distal positions 9 was observed for quinolines and isoquinoline. This direct alkylation reaction is complimentary to the deoxygenative ortho -alkylation of heterocyclic N -oxides.…”
mentioning
confidence: 99%